2016
DOI: 10.1136/bcr-2015-214284
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib improves insulin sensitivity and affects lipid metabolism in a patient with chronic myeloid leukaemia

Abstract: A 65-year-old woman had been visiting our department for the treatment of type-2 diabetes mellitus since December 2012. Her glycated haemoglobin levels were well controlled (≈5.8% (40 mmol/mol)) by metformin (500 mg). In July 2014, her white cell count increased suddenly to 33 530 cells/μL and she was diagnosed with Ph+ chronic myeloid leukaemia. She was started on dasatinib (100 mg), which immediately normalised plasma levels of WCC. Dasatinib improved the glycaemic index to <6.0% and also improved plasma lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…A previous retrospective cohort study found that dasatinib treatment lowers mean serum glucose values by 52 mg/dL regardless of T2DM status, 9 whereas prior case reports have found improvements including remission of preexisting T2DM. 5,6,8,17,18 Our finding of an absolute improvement of serum glucose values by 31.4 mg/dL, including 2 of 4 patients who no longer required insulin within 12 months of dasatinib initiation, is consistent with prior literature on the antidiabetic properties of dasatinib. Retrospective cohort studies are conflicting about the impact of imatinib on glycemic control, with some reporting a modest improvement in serum glucose concentration (9 mg/dL) 9 and other studies reporting no improvement.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A previous retrospective cohort study found that dasatinib treatment lowers mean serum glucose values by 52 mg/dL regardless of T2DM status, 9 whereas prior case reports have found improvements including remission of preexisting T2DM. 5,6,8,17,18 Our finding of an absolute improvement of serum glucose values by 31.4 mg/dL, including 2 of 4 patients who no longer required insulin within 12 months of dasatinib initiation, is consistent with prior literature on the antidiabetic properties of dasatinib. Retrospective cohort studies are conflicting about the impact of imatinib on glycemic control, with some reporting a modest improvement in serum glucose concentration (9 mg/dL) 9 and other studies reporting no improvement.…”
Section: Discussionsupporting
confidence: 89%
“…Sporadic case reports suggested that TKIs, primarily imatinib, may improve glycemic control or even result in complete remission of T2DM. [3][4][5][6][7][8] A subsequent retrospective cohort study of patients with (n¼17) and without (n¼61) T2DM found that treatment with various TKIs (sunitinib, sorafenib, dasatinib, and imatinib) was associated with lower serum glucose levels. This finding was limited by a small T2DM cohort, heterogeneous malignant neoplasms, and possible confounding by progression of the malignant disease and weight changes.…”
mentioning
confidence: 99%
“…In both imatinib- and dasatinib-treated patients, increased circulating adiponectin e level correlates with decreased insulin resistance. 57 58 This correlation might be explained by the translocation of the glucose transporter GLUT4 f from the cytoplasm to the cell membrane following adiponectin signaling. 59 Additionally, adiponectin has been related to decreased hepatic glucose production which could be an additional mechanism by which imatinib and dasatinib improve glucose metabolism.…”
Section: Metabolic Dysregulationmentioning
confidence: 99%
“…It has been found that dasatinib might have positive as well as negative effects on the metabolism of glucose and lipids. 33 All these correlations were significant (P < 0.01). The drug-ME correlation matrix was provided in Tables S4 and S5.…”
Section: Dovepressmentioning
confidence: 87%